Indonesian Flipbook-Based Educational Magazine with Regional Decorations for Fifth Grade Elementary School - Yani, Candrika Deva; Setiawan, Deni (Universitas Pendidikan Ganesha, 2024)
This research is motivated by learning problems, especially in terms of students' knowledge of regional decorative materials. This problem occurs due to students' lack of understanding of regional decorative material, causing student learning outcomes to not reach the KKM. This research aims to develop flipbook-based educational magazine media containing Indonesian language in improving student learning outcomes on regional decoration material for fifth grade elementary school students. The method used in this research is research and development research using the Borg and Gall development model. Product validity testing is carried out with material expert validators and media expert validators. The research results showed that the results of the media feasibility test were 86% with the predicate